Upaya Pembentukan Sikap Kepedulian Sosial Siswa Melalui Internalisasi Nilai-Nilai Akhlak di Sekolah - Hery Susanto; Badruzzaman M. Yunus; Ahmad Sukandar (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine and analyze the strategy of internalizing moral values ​​in an effort to form social awareness of students at SMKN 1 Majalaya, Bandung Regency. This research method uses a qualitative type with a descriptive approach. Data collection techniques used are observation, interviews and documentation. The results of the research include: (1) Planning, observing school conditions and situations, making the concept of internalizing moral values ​​in each lesson, organizing learning resources, and determining learning evaluations. (2) Implementation, in the classroom by giving motivation and advice and outside the classroom with religious activities, namely the habituation of the dhuha prayer in congregation through the Extracurricular of the Mosque Youth Association, Tahfidz Qur'an, Social Service, Holding recitations by bringing in speakers from outside, Listening to the murotal reading before the KBM. (3) Evaluation, evaluation context assessment, input assessment, process assessment, product/outcome assessment. The implication for the formation of a caring attitude of students is that they are accustomed to worshiping, respecting teachers, familiarity with other friends, having concern for others who are affected by disasters, being tolerant, and obeying the rules.